(untitled) (Linguist, 2021)
The article, which we have translated here, consists of a reflection on the subject of the argumentation of the French linguist Patrick Charaudeau who supports the idea that the argumentation must be addressed according to the particular context of the communication situation, believing that the argumentative value of an act of discourse cannot be judged or evaluated outside its conditions of production. Illustrating his demonstration from various examples borrowed mainly from the political scene, the author recalls that political communication seeks above all consensus and that, in doing so, the argument on which it is based is largely built on common values, on public opinion. Oscillating between the order of reason and the order of passion, the political discourse, just like advertising discourse, is a persuasive staging in which ethos and pathos carve out the lion’s share, leaving to the logos the congrue part.